Oil-soluble ionic liquids as antiwear and extreme pressure additives in poly-α-olefin for steel/steel contacts - Huang, Guowei; Yu, Qiangliang; Ma, Zhengfeng; Cai, Meirong; Zhou, Feng; Liu, Weimin (Friction, 2019)
To enhance the lubricating and extreme pressure (EP) performance of base oils, two types of oil-soluble ionic liquids (ILs) with similar anion albeit dissimilar cations were synthesized. The physical properties of the prepared ILs were measured. The anticorrosion properties of ILs were assessed by conducting corrosion tests on steel discs and copper strips, which revealed the remarkable anticorrosion properties of the ILs in comparison with those of the commercial additive zinc dialkyldithiophosphate (ZDDP). The tribological properties of the two ILs as additives for poly-α-olefin-10 (PAO10) with various mass concentrations were investigated. The tribological test results indicate that these ILs as additives are capable of reducing friction and wear of sliding contacts remarkably as well as enhance the EP performance of blank PAO10. Under similar test conditions, these IL additives exhibit higher lubricating and anti-wear (AW) performances than those of ZDDP based additive package in PAO10. Subsequently, X-ray photoelectron spectroscopy (XPS) and energy dispersive spectrometer (EDS) were conducted to study the lubricating mechanism of the two ILs. The results indicate that the formation of tribochemical film plays the most crucial role in enhancing the lubricating and AW behavior of the mixture lubricants.